Hinduism Teachings in the Story of Ni Diah Tantri - I Made Luwih; I Ketut Sudarsana (Jayapangus Press, 2021)
The study aimed to determine the narrative structure in Ni Diah Tantri’s story and its Hindu religious teachings. Data collection in this study used a literature study. Several techniques carried out data analysis in this study. These were descriptive techniques, qualitative techniques, interpretation, checking the data validity, presenting data (data display), and concluding (verification). The study results show that the teachings contained in the story of Ni Diah Tantri were a form of tendency from the author, which is very useful for readers. The Hindu religious teachings in the story of Ni Diah Tantri consist of self-control, especially lust which is influenced by the thoughts of Sang Prabhu Eswaryadala. The next teaching was Ni Diah Tantri’s teachings of love who truly sympathize and her love for his father so that Ni Diah Tantri is willing to be handed over to Sang Prabhu Eswaryadala. Last, the teachings of loyalty from Ki Patih Bandeswarya to Sang Prabhu Eswaryadala. Ki Patih Bandeswarya’s loyalty to Sang Prabhu Eswaryadala was manifested by Ki Patih’s obedience to the king’s orders to offer beautiful girls every day for marriage.